The newest methods of fires detection - Shchipitsyn, С.М. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
Designs and principles of action of fire detectors, developed and produced by «Systems Sensor Control Fire Detectors» Ltd. are submitted. The special attention is given to the new generation of detectors – laser aspiration fire detectors, considerably raising a level of fire protection of objects and constructions of various types.